2016
DOI: 10.1002/jcla.21969
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabonomics of Mild Acute Pancreatitis

Abstract: Metabonomic analysis has revealed eight metabolites with potential diagnostic values toward MAP, among which four metabolites can be used to monitor the disease course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Previous studies have also demonstrated that changes in bile acids, phosphatidylcholine, and amino acids occur in acute pancreatitis [ 27 , 31 , 32 ], thus confirming our present findings. However, few researchers have investigated differences in metabolites between severe and mild cases.…”
Section: Resultssupporting
confidence: 93%
“…Previous studies have also demonstrated that changes in bile acids, phosphatidylcholine, and amino acids occur in acute pancreatitis [ 27 , 31 , 32 ], thus confirming our present findings. However, few researchers have investigated differences in metabolites between severe and mild cases.…”
Section: Resultssupporting
confidence: 93%
“…That study identified citrate as the primary metabolite associated with the inflammatory AP state and alcohol consumption. Xu et al [ 29 ] studied the serum metabolomics of mild AP in 38 patients. Although the authors did not specify the etiology of AP patients, by using the chromatography-high-resolution mass spectrometry (UPLC-HRMS) technique, they identified decanyl choline, dodecanol, and 2-tetradecanone as diagnosis metabolites, and sphinganine, L-thyronine, glycocholic acid and 2-tetradecanone as therapeutic response metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…It adopted metabolic profiling methods for the comprehensive analysis of biological fluids, and has a great impact on the investigation of discovering biomarkers, and identifying perturbed pathways due to disease or drug treatment. Recently, some reports have described metabolomic studies using various techniques, among the analytical techniques in metabonomic research, UPLC-MS has demonstrated its great potential essentially due to the high reproducibility of measurements and sensitivity of analysis (Ramirez et al, 2013; Lee et al, 2015; Xu et al, 2016). In recent years, metabolomics technology has also contributed to the study of the mechanism of drug action.…”
Section: Introductionmentioning
confidence: 99%